2005
DOI: 10.1080/13102818.2005.10817194
|View full text |Cite
|
Sign up to set email alerts
|

Lessons from the Microsatellite Characterization of a Segregating Population Derived from Seeds of open PollinatedRosa Damascena Mill. F. TrigintipetalaPlants

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 9 publications
0
8
0
Order By: Relevance
“…Probably the complex genetics of this species is the reason that R. damascena shows low affinity to self-pollination and cross-pollination. however, Rusanov et al (45) reported that it is easy to create a segregating population of self-pollinated Rosa damascena through collection of seeds from industrial fields since the obtained seeds are the result of either selfpollination or pollination with neighbouring plants possessing the same genotype. this creates a good opportunity for start of genetics studies based on segregation of DnA markers and their association with the plant phenotypes.…”
Section: Perspectives For Marker Assisted Breedingmentioning
confidence: 99%
“…Probably the complex genetics of this species is the reason that R. damascena shows low affinity to self-pollination and cross-pollination. however, Rusanov et al (45) reported that it is easy to create a segregating population of self-pollinated Rosa damascena through collection of seeds from industrial fields since the obtained seeds are the result of either selfpollination or pollination with neighbouring plants possessing the same genotype. this creates a good opportunity for start of genetics studies based on segregation of DnA markers and their association with the plant phenotypes.…”
Section: Perspectives For Marker Assisted Breedingmentioning
confidence: 99%
“…Iran was pointed out as a centre of genetic diversity of this species, (2,16). In our recent study (24) we concluded that Rosa damascena is most probably a segmental allotetraploid species with a type of inheritance (disomic or tetrasomic) depending on the position of the locus in the genome.…”
Section: Genotyping Of the Available Genetic Resources Of Rosa Damascenamentioning
confidence: 95%
“…Thus, one might assume a hybrid origin. Rusanov et al, 34 concluded that R. damascena is most probably a segmental allotetraploid species with a type of inheritance (disomic or tetrasomic) depending on the position of the locus in the genome. Evaluation of genetic diversity of R. damascena based on morphological characteristics is very difficult because of large number of morphological characters, and it is a time consuming method.…”
Section: Evaluation and Genetic Diversitymentioning
confidence: 99%
“…That is why DNA markers have been applied for characterization of rose genetic diversity 5,[35][36][37][38][39][40][41][42] . Now amplified fragment length polymorphisms (AFLT) approach is a reliable, rapid and sensitive technique for detecting genetic diversity of Damask rose genotypes 34,43 . Agaoglu et al, 44 and Baydar et al, 34 used RAPDs and AFLPs techniques to study the genetic diversity of R. damascena and found genetic uniformity of the R. damascena cultivars grown in Turkey.…”
Section: Evaluation and Genetic Diversitymentioning
confidence: 99%
See 1 more Smart Citation